Discriminating scheelite deposit types using interpretable ensemble learning: A case study from the Xuefengshan Au-Sb-W belt, South China - Xiao-Ran Zhou; Qi-Liang Liu; Biao Liu; Jing-Hua Wu; Safiyanu Muhammad Elatikpo; Fei Deng; Shiwei Cui (Journal of Geochemical Exploration, 2026)

Genome-wide meta-analysis with 1,590,596 individuals identifies 12 novel risk loci for systemic lupus erythematosus - Gaizhi Zhu; Wenting Su; Jiahui Deng; Bing Zhai; Ran Gao; Jinming Qiu; Keqi Gu; Ziqing Bian; He Xiao; Guoming Luan; Renxi Wang (Mammalian Genome, 2026)

Deep eutectic hybrid solvent-functionalized MOF for ultrasensitive electrochemical detection of ultrashort-chain PFAS in food - Wanlin Deng; Chen Fan; Ming Jin; Ran Duan; Jie Li (Food Control, 2026)

Inverse identification of wind turbine horizontal thrust on steel-concrete hybrid tower using intelligent algorithm - Shou-Zhen Li; Yu-Hang Wang; Jinjin Wang; Ran Deng; Chao Hu; Liming Jiang (Engineering Structures, 2026)

T-section stiffeners for enhanced ductility of flat-sided FRP-confined double-skin tubular columns: Concept and demonstration - Ran Deng; Zhe Zhang; Tao Yu (Engineering Structures, 2026)

Simultaneous elimination of sulfonamides and antibiotic resistance genes via peroxymonosulfate activation by ligand-modulated iron sites on biochar: The critical role of interfacial EDTA complexation - Yifan Liu; Fengxia Yang; Xue Li; Zhikang Deng; Xi Chen; Minghui Xiang; Ran Zhao; Xiaoquan Mu; Yongzhen Ding; Junjie Wang; Zulin Zhang (Chemical Engineering Journal, 2026)

Urban ecological environment quality and brain aging: epidemiological evidence from a middle-aged and elderly population-based cohort - Zihuan Shao; Shenghao Yuan; Jiawei Gu; Yujia Bao; Jingyun Feng; Hongxuan Wu; Wenqi Qian; Dayi Lai; Tianlang Tong; Chen Shen; Xiaobei Deng; Jinjun Ran (Sustainable Cities and Society, 2026)

Comparative transcriptome analysis identifies ABA/ethylene signaling components and WGCNA hub genes underlying defoliant sensitivity in Gossypium barbadense - Caixia Li; Meng Wang; Zixin Zhou; Zhiqing Liu; Jianping Li; Yaohua Li; Yahui Deng; Yifan Wang; Lingfang Ran; Jiahui Zhu; Alifu Aierxi; Weiran Wang; et al. (Plant Gene, 2026)

Tailored micro-encapsulation for food technology: A review on the fabrication and application of core-shell microcapsules - Ran Tu; Jiawang Jin; Yan Li; Chenggang Deng; Qinhong Wang (Trends in Food Science & Technology, 2026)

Retraction notice to “Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China” [Sci. Total Environ. 897 (2023) 165394] - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2026)

The impact of atmospheric aging processes on the ice nucleation activity of Asian dust: A perspective from online continuous flow diffusion chamber observations - Jiayun Li; Xinyuan Chang; Dantong Chen; Kai Bi; Yunbo Chen; Xincheng Ma; Ruijie Li; Ping Tian; Mengyu Huang; Xiaoyu Ren; Shuai Wang; Zhaoze Deng; et al. (Atmospheric Pollution Research, 2026)

Global GNSS IWV diurnal variability over 6,000 stations and its implications for assessing the impact of artificial ERA5 discontinuities - Peng Yuan; Geoffrey Blewitt; Corné Kreemer; Zhao Li; Ran Lu; Pengfei Xia; Weiping Jiang; Harald Schuh; Jens Wickert; Zhiguo Deng (GPS Solutions, 2026)
The diurnal cycle of Integrated Water Vapor (IWV) plays a key role in radiation, convection, and land–atmosphere interactions, yet its global characteristics and representation in atmospheric reanalysis products remain insufficiently quantified. Using a decade of GNSS observations from more than 6,000 stations, this study characterizes the global IWV diurnal variability and assesses the performance of ERA5 in reproducing these signals. GNSS IWV exhibits a coherent diurnal cycle dominated by the S₁ (24 h) harmonic, with annual-mean amplitudes decreasing from 3 kg m⁻² in the tropics to near zero at high latitudes, a global mean of 0.40 kg m⁻², and peak times clustered around 17.4 local time; the semidiurnal S₂ (12 h) component is weaker but similarly systematic. In contrast, ERA5 exhibits sharp artificial discontinuities at the transition times (09–10 and 21–22 UTC) of its 12-hour assimilation windows, affecting 54% of stations and reaching magnitudes that are 146% of the standard deviation of observed diurnal anomalies. These discontinuities distort the estimated diurnal cycle, producing a median S₁ phase lag of 1.1 h relative to GNSS and weakening S₂ amplitude agreement, with the coefficient of determination (R²) decreasing from 0.48 to 0.38. The results highlight both the robustness of GNSS IWV as a benchmark and the need for caution when using ERA5 for diurnal-cycle applications.

Bromine-directed crystallization of phenazine acceptors enables high-efficiency organic solar cells approaching 20% PCE in green solvents - Yingjie Xie; Yaonan Ma; Peng Mao; Tong Wang; Nan Yi; Yue Wang; Xinya Ran; Huijuan Bi; Hui Wang; Dingding Qiu; Yilan Zhai; Caixuan Wang; et al. (Chemical Engineering Journal, 2026)

Hyaluronic acid-based supramolecular peptide-drug conjugate prodrug nanosystems for precise multiple myeloma therapy - Xiangyu Deng; Qili Huang; Li Cao; Ran Luo; Wenyan Wang; Hongzhong Chen; Chendi Ding; Lina Su; Lin Mei (Carbohydrate Polymers, 2026)

Retail wet markets, food handlers, and hospitalised patients as nodes in a shared non-typhoidal Salmonella ecosystem: a one health molecular epidemiological pilot study in Wuhan, China - Feng Tang; Zhi Chen; Shiyong Deng; Xiaomei Wang; Xuyang Gong; Ran Li; Lei Xi; Changzhen Li; Baoxiang Wang; Wanjun Luo (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Navigating the trade-off: Thermal hydrolysis as a winning pretreatment for simultaneously enhancing methanogenesis and immobilizing cadmium in waste activated sludge - Baowei Zhang; Xiang Tang; Yizhan Deng; Ruobin Wang; Mengqi Wei; Zezhong Ran; Changzheng Fan (Journal of Hazardous Materials, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Preparation of porous DAP-IPA-POPs for efficient adsorptive removal of organochlorine pesticides - Shirui Zhao; Zhenxiang Jiang; Yunshuang Hu; Yingzhu Yang; Zhixia Li; Zhaojin Ran; Zhongmin Wang; Yiting Wang; Hua Cen; Guang Deng (Journal of Environmental Chemical Engineering, 2026)

Deep eutectic solvent-based ultrasonic-assisted extraction of polyphenols from Macadamia integrifolia green peel: COSMO-RS screening, process optimization, and its application in chitosan/polyvinyl alcohol films - Ming Zhang; Yang Yang; Jian Qiao; Ya Li; Ran Kong; Jianfei Kuang; Lingdong Li; Changbin Wei; Xu Deng; Li-qing Du; Xixiang Shuai (Food Chemistry, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Synergistic Effects of Reduced Phosphorus Fertilization and Phosphate-Solubilizing Bacteria on Available Phosphorus Release, Plant Growth, and phoD-Associated Bacterial Processes in Tunnel Waste Slag - Shuwei Zhao; Jing Li; Yixuan Li; Xin Tian; Ran Deng (Current Microbiology, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Hyphosphere metabolic reprogramming in lipids and aromatic amino acids drives differential mycorrhizal growth promotion in trifoliate orange - Hao-Ran Jiang; Wan-Lin Fu; Ci Deng; Ying-Ning Zou; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

Prediction of overpressure from hydrogen cloud explosions: A study from open space to hydrogen refueling and filling station scenarios - Qiuhong Wang; Bin Peng; Jun Deng; Wei Gao; Jianyi Chen; Hongxiang Wan; Mingshu Bi; Ran Liu; Chaoyuan Hu (Process Safety and Environmental Protection, 2026)

Identifying active nitrate-assimilating bacteria that alleviate secondary salinization in facility soil driven by carbon source availability - Qian Wang; Ran Liu; Cheng Chu; Yunbin Jiang; Huan Deng; Xinqi Huang; Cheng Han; Wenhui Zhong (Journal of Cleaner Production, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

The impacts of three types of hydrological changes on the human health risks of soil antibiotic resistance genes in Dongting Lake wetlands, China - Haipeng Wu; Guxiang Xu; Juan Dai; Zenghui Peng; Fengwei Ran; Yijie Deng; Na Zhang (Journal of Hazardous Materials, 2026)

Summertime characteristics and in-situ photochemistry of volatile organic compounds in a high-altitude region in central China: Implications of regional transport - Zhaoqi Wang; Chunmian Yang; Haibin Huang; Mengjie Deng; Jiapeng Ran; Xiaoxiao Li; Xiaofen Pei; Han Yue; Hairong Cheng (Atmospheric Research, 2026)

Spatiotemporal Variation Analysis of Yangtze River Basin Water Quality in Chong Qing, China During 2021–2023 Based on Improved Water Quality Assessment - Libo Ran; Xing Wei; Yulin Zhou; Qingmei Zhang; Yanan Fu; Zikan Deng (Water, Air, & Soil Pollution, 2026)

Typical application studies of thermal management technology in nuclear reactor - Youyou Xu; Jian Deng; Dahuan Zhu; Qi Lu; Jia Liu; Wei Zeng; Xu Ran; Zhifang Qiu; Dongwei Wang (Annals of Nuclear Energy, 2026)

Rhein Prevents APAP-induced drug-induced Liver Injury by Upregulating Nrf2 and Inhibiting APAP-activating Enzymes - Mingda Liu; Jin Dai; Liangding Dou; Zifeng Deng; Junxian Liu; Xin Hou; Jinwen Zhang; YongChao Huang; Zhi Huang; Dai Wang; Dongbei Guo; Ran An; et al. (Cell Biochemistry and Biophysics, 2026)

Enhanced bacteria-fungi associations and soil microbial network stability underpin ecosystem multifunctionality across a 53-year desert restoration chronosequence - Qingqing Hou; Muhammad Aqeel; Longwei Dong; Jie Peng; Ying Sun; Fan Li; Dong Tang; Bodong Yuan; Xusheng Guo; Jinzhi Ran; Weigang Hu; Xinrong Li; et al. (Journal of Environmental Management, 2026)

Modulating the multiscale structure and digestibility of OSA starch by phenolic acid substituents and heating process - Ran-Ran Deng; Ran Feng; Han Tao; Bao Zhang (Food Chemistry, 2026)

Bending-shear interaction in tapered concrete-filled double-skin steel tubular columns with large void ratios - Wei Ren; Ou Zhao; Yu-Hang Wang; Ran Deng (Engineering Structures, 2026)

Effect of Mg(OH)2 addition on NH4H2PO4 powder in suppressing the explosion of volatile mixtures of methane and coal - Qiuhong Wang; Rui Guo; Jun Deng; Zhenmin Luo; Chi-Min Shu; Zezhou Song; Qingfeng Wang; Junjie Wu; Di Wu; Ran Liu (Chemical Engineering Journal, 2026)

A combinatorial stress-alleviation strategy for efficient β-carotene production in Escherichia coli - Yuanqing Ji; Jingyu Yue; Yihong Huang; Ran Li; Shasha Zhong; Xi Jiang; Shimin Zhang; Yuhong Zou; Aihua Deng; Shiyan Qiao (Bioresource Technology, 2026)

Flow characteristics and structural optimization of uniform air supply duct systems in subway stations for improving airflow uniformity - Wanqing Zhang; Xiongwei Deng; Angui Li; Fangting Du; Changqing Yang; Ran Gao; Haiguo Yin; Zhuowei Zhang (Building and Environment, 2026)

A two-stage ship path planning method based on trial maneuvers - Yangyu Zhou; Shuxiu Liang; Qiaofeng Ma; Qingren Xue; Jia Li; Ziyu Deng; Ran Yan (Ocean Engineering, 2025)

The influence of differently aged microplastics on electrochemical degradation efficiency - Ran Chen; Yining Deng; Jinyan Wang; Yuchun Cui; Yuzeng Zhao; Honghua Ge (Journal of Environmental Management, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Development of novel melatonin-isatin hybrids as multifunctional agents for Alzheimer’s disease - Ying-Ying Zhong; Jun‑Ze Deng; Qin Wang; Li Chen; Zi-Hang Yang; Ya-Mei Zhang; Lu‑Yi Zhou; Yi-Ran Li; Jia-Qiang Wu; Xiao-Qin Wang (Molecular Diversity, 2025)

Machine Learning Improves Mesoscale Offshore Wind Resource Assessment over the Yellow Sea - Haixing Gong; Kan Yi; Dinghua Yang; Wenyu Huang; Chenqing Fan; Ran Hao; Lina Sha; Mengke Deng; Hao Zhang (Journal of Meteorological Research, 2025)

The Increased Effect of Spring Leaf Unfolding on Autumn Senescence in the Northern and Southern Hemispheres - Dong Tang; Shubin Xie; Jie Peng; Ying Sun; Abraham Allan Degen; Yuan Sun; Jiali Luo; Zifan Li; Yaning Kuang; Lixue Wei; Weigang Hu; Longwei Dong; et al. (Global Ecology and Biogeography, 2025)
Aim To investigate the contributions of vegetation growth carryover (VGC, defined as the effect of present states of vegetation growth on subsequent phenophases) and climatic factors to plant phenology, particularly start‐of‐season (SOS) and end‐of‐season (EOS), and how these contributions have evolved globally over the past four decades. Location Global, with a focus on the Northern Hemisphere (NH) and Southern Hemisphere (SH). Time Period 1963–2015 for ground observations, 1982–2022 for satellite NDVI data, and 1982–2022 for climate data (temperature, precipitation, radiation, and potential evapotranspiration). Major Taxa Studied Global vegetation, without specifying individual species. Methods We analysed two sets of satellite‐derived NDVI data, ground‐based phenological observations, and long‐term climate data (temperature, precipitation, radiation, and potential evapotranspiration). Statistical models quantified the contributions of climatic factors and VGC to phenology trends. Results Globally, advanced SOS was driven primarily by increasing temperature and radiation, while delayed EOS was attributed to rising temperature and the carryover effect of spring vegetation growth (VGC SOS ). VGC SOS was the dominant driver of EOS in the SH, whereas temperature played a larger role in the NH. Over the past four decades, the contribution of VGC SOS to EOS has increased significantly on a global scale. However, the SH experienced pronounced “warming and drying” trends, which weakened the relative contribution of VGC SOS to EOS compared to climate‐driven delays. Main Conclusions VGC SOS plays a substantial role in shaping EOS in both hemispheres, with its importance increasing over time. These findings improve our understanding of vegetation dynamics and offer valuable insights for predicting vegetation growth and carbon sequestration under future global warming scenarios.

Assessment of flood risk in jinsha river basin based on land use value and PSR model - Xiao Chen; Ran Zhai; Wen Fang; Liwen Xu; Lili Liang; Juanru Yang; Hanlin Man; Zhenyu Lv; Chao Wang; Deng Liu; Mengqing Cui (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Explainable transfer learning for subsurface soil moisture prediction - Sheng Ye; Yifan Chai; Jiyu Li; Jingkai Wang; Xuebin Deng; Qihua Ran (Journal of Hydrology, 2025)

Construction of OSA-starch and caffeic acid composite system driven by high pressure homogenization: Multiscale structural evolution and digestibility regulation mechanism - Ran-Ran Deng; Ran Feng; Ran Meng; Si-Jie Wu; Han Tao; Bao Zhang (Food Chemistry, 2025)

Excessive health risks of summer aerosol sources related to particle-bound toxic metals in the Tibetan Plateau, China - Jiwei Li; Yunfei Wu; Zhaoze Deng; Liang Ran; Yunjie Xia; Jianchun Bian; Renjian Zhang; Yang Yu; Jiutao An (Environmental Pollution, 2025)

Molecular Cloning and Expression Profiling of a Bax-Homologous Gene (EsBax) in the Chinese Mitten Crab (Eriocheir sinensis) Under Exogenous Stimulations - Mingqiao Ran; Chao Liu; Ying Deng; Wenbin Liu; Dingdong Zhang; Hengtong Liu; Cheng Chi (Fishes, 2025)
EsBax (bcl-2 Associated X protein), a member of the bcl-2 family involved in the mitochondrial apoptosis pathway, plays a crucial role in immune response and defense in invertebrates. In this study, we successfully cloned the full-length cDNA of EsBax from the Chinese mitten crab (Eriocheir sinensis) and investigated its immune-related functions. The EsBax cDNA is 3374 bp in length, including a 1563 bp open reading frame (ORF) encoding 521 amino acids, a 142 bp 5′ untranslated region (UTR), and a 1699 bp 3′ UTR. The predicted EsBax protein has a molecular weight of 58.0786 kD, a theoretical isoelectric point of 7.28, and contains three conserved BH domains (BH1-BH3), and a transmembrane domain (TM). Amino acid sequence analysis revealed the highest sequence identity (99.42%) with E. sinensis. For the expression analysis, three biological replicates were performed for each tissue and treatment group. Real-time quantitative PCR showed that EsBax mRNA was ubiquitously expressed in all examined tissues, with the highest expression in the hepatopancreas, followed by hemocytes, intestine, gill, and the lowest in muscle. Upon stimulation with lipopolysaccharide (LPS), Aeromonas hydrophila (AH), or cycloheximide (CHX), EsBax expression increased and peaked at 24 h (LPS and CHX) or 48 h (A. hydrophila), then decreased. These results suggest that EsBax expression is dynamically responsive to exogenous stimulants (LPS, A. hydrophila, and CHX) in E. sinensis, implying a potential role of EsBax in the molecular events associated with pathogen-induced apoptosis in this species.

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Insights into toxic elements mobilization in Karstic paddy soil of southwest China: The overlooked significance of iron-organic matter colloids - Ran Wei; Junbin Liu; Ming Li; Weipeng Xie; Jingjing Li; Lirong Liu; Yanjun Jiang; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; et al. (Environmental Pollution, 2025)

Interfacial fluid manipulated strategies: Flexible polyaniline film with artificial microstructure for multifunctional sensing of physical and chemical stimuli - Shuhuan Deng; Yukang Peng; Jingjie Zhou; Jiajie Huang; Zhongtao Qin; Yangguang Ran; Ningjing Wang; Enchong Ning; Lilin Shen; Yulin Hu; Wenbo Chen; Qinping Qiang; et al. (Chemical Engineering Journal, 2025)

Biomass-derived organic aerogels endowed flexible polyurethane foam with excellent flame retardance, smoke suppression, bacteriostasis and enhanced mechanical property - Ying-Ming Li; Yao Deng; Hang-Ping Fang; Yi-Ran Li; De-Yi Wang (Chemical Engineering Journal, 2025)

CdS-mediated electron dynamics in light-assisted anaerobic digestion: Simultaneous cadmium sequestration and methane enrichment by alkali pretreatment - Baowei Zhang; Xiang Tang; Linrui Zhong; Jiangfu Zheng; Huannian Xiao; Yizhan Deng; Zezhong Ran; Mengqi Wei; Lifang Liu; Changzheng Fan (Journal of Hazardous Materials, 2025)

Myricetin and 2-amino-3-methyl-3H-imidazole [4, 5-F] quinoline triggers liver injury by regulating gut microbiota and liver metabolism - Hongting Deng; Yanan Zhao; Ran Cao; Leyao Chen; Chang Zhang; Hui Teng; Lei Chen (Journal of Hazardous Materials, 2025)

Garlic-derived exosomes attenuated fibroblast differentiation by inhibiting PFKFB3 expression in TNBS-induced mice - Jinfan Liu; Juan Deng; Shuang Xiong; Wentao Wu; Siyuan Zhou; Hongyan Ran; Fei Yin; Jianhui Liu (Food Bioscience, 2025)

Associations of phthalate metabolites in urine and follicular fluid with endometrial thickness in the TREE cohort - Xiu-Ting Li; Chong Liu; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; A.-Xue Liu; Yang-Juan Li; Jin-Qin Zhu; Ning Zhang; Juan Li; et al. (Environmental Toxicology and Pharmacology, 2025)

Morphological and physiological responses to aridity in narrowly- and widely-distributed plant species in drylands - Junlan Xiong; Weigang Hu; Allan Degen; Jie Peng; Longwei Dong; Li Yan; Qingqing Hou; Shuran Yao; Ying Sun; Xiaoting Wang; Yahui Zhang; Yan Deng; et al. (Science China Life Sciences, 2025)

Zhengella sedimenti sp. nov. and Phycobacter sedimenti sp. nov., two novel bacteria isolated from coastal sediment with genomic and metabolic analysis - Pei-Ran Lin; Li-Jia-Yu Deng; Han-Zhe Zhang; Le Liu; Tian-He Liu; De-Chen Lu; Zong-Jun Du (Antonie van Leeuwenhoek, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

2D ferroelectric perovskite for efficient and stable perovskite solar cells - Xia Chen; Chunyan Deng; Jihuai Wu; Yitian Du; Ran Ji; Zongbao Zhang; Angelika Wrzesińska-Lashkova; Lina Tan; Liuxue Sun; Yuelin Wei; Yunfang Huang; Yana Vaynzof; et al. (Chemical Engineering Journal, 2025)

A versatile and double cross-linked hydrogel with potent antibacterial and immunomodulatory Zn@Met nanocomplexes for enhanced diabetic-infected wound healing - Tinglong Chen; Xueliang Zhang; Shengzhe Zhou; Dong Fang; Dinghao Luo; Zhaoyang Ran; Yingchun Liu; Cheng Xu; Jinhao Cao; Xiaodong Li; Yongqiaong Hao; Xiaoqing Wang; et al. (Chemical Engineering Journal, 2025)

Corrigendum to “Neovascularization-directed bionic eye drops for noninvasive renovation of age-related macular degeneration” [Chem. Eng. J. 450 (2022) 138291] - Meixin Ran; Yaxin Deng; Jiaqi Yan; Anan Zhang; Ying Wei; Xiaowen Li; Haibing He; Jingxin Gou; Tian Yin; Xing Tang; Jun Kong; Han Zhang; et al. (Chemical Engineering Journal, 2025)

Distribution Range and Richness of Plant Species Are Predicted to Increase by 2100 due to a Warmer and Wetter Climate in Northern China - Ying Sun; Yan Deng; Shuran Yao; Yuan Sun; Abraham Allan Degen; Longwei Dong; Jiali Luo; Shubin Xie; Qingqing Hou; Dong Tang; Yuzhen Sun; Junlan Xiong; et al. (Global Change Biology, 2025)
The warming global climate is threatening terrestrial ecosystem stability, including plant community structure and diversity. However, it remains unclear how distribution, richness, and turnover of plant species are impacted by warming and wetting in northern China. In the present study, species distribution models were applied to predict the spatial distribution of 5111 plant species based on 111,071 occurrence records in northern China. Additionally, variations in species richness and turnover rates were predicted for 2100 under 3 scenarios. The results indicated that approximately 70% of plant species will expand in their distribution, resulting in an increase in species richness. These changes will be driven mainly by temperature seasonality (TSN), annual precipitation (MAP), and mean temperature of the coldest quarter (MTCQ). However, about 30%–40% of the species will face extinction risks, including a considerable number of endemic and Red‐Listed species, and suitable habitat loss (LSH) will exceed 30%. Narrow‐ranging species will be more likely to lose a larger percentage of their suitable habitats than wide‐ranging species, highlighting their sensitivity to environmental changes. Importantly, it emerged that species turnover rates will increase linearly with ecological vulnerability at the grid level, indicating that community structure and species composition are easily affected by climate change in ecologically vulnerable areas. Therefore, biodiversity hotspots with high species richness in the southern study areas, as well as regions exhibiting both fast species turnover and significant ecological vulnerability, should be prioritized for conservation. These findings provide insights into how species composition and richness in plant communities vary with global climate change and provide effective ecological conservation and management strategies.

Constructing a Li+-rich interlayer onto lithium anode for boosting the performance of high-voltage all-solid-state lithium metal batteries - Jinhai Liu; Kexin Liang; Linyuan Ma; Ran Bi; Yuanfu Deng (Chemical Engineering Journal, 2025)

Persistent influence of dust on aerosol properties in summer over the northeast Tibetan Plateau explored by surface and tethered balloon-borne observations - Liang Ran; Zhaoze Deng; Yunfei Wu; Zhixuan Bai; Wanyun Xu; Xuelian Xu; Shengcang Wang; Ping Tian; Mengyu Huang; Xiangao Xia; Jianchun Bian (Atmospheric Environment, 2025)

The growth performance in different seasons of Homatula variegata (Dabry de Thiersant, 1874) in Northern Guizhou, China - Gui Bang Xiao; Qi Wei Guo; Wei Xi Deng; Qi Qi Xiao; Lin Zhou; Hao Ran Zhang; Jia Lin; Ding Zhi Fang (Journal of Comparative Physiology B, 2025)

The effects of different types of surfactants on the electrochemical degradation of PET microplastics - Ran Chen; Yining Deng; Jinyan Wang; Yuchun Cui; Yuzeng Zhao; Honghua Ge (Journal of Water Process Engineering, 2025)

Emergy-based sustainability analysis and comprehensive evaluation of individual heating systems: A case study from rural northern China - Yun Deng; Xueling Ran; Yaohong Yu; Yongkun Fu; Sihao Ren; Mingyang Liu; Renjie Dong; Yuguang Zhou (Journal of Cleaner Production, 2025)

Electrostatic self-assembly assisted construction of MXene/MoO3 hybrid aerogel for free-standing supercapacitor electrodes - Feitian Ran; Bowen Tan; Meijie Hu; Shulin Deng; Kai Wang; Wanjun Sun; Jifei Liu; Xiaobin Yang (Chemical Engineering Journal, 2025)

Manganese on P, N self-doped biochar toward promoting periodate activation for highly efficient tetracycline degradation: Performance and mechanisms - Xiaofang Pan; Hong Ma; Rongning Zhang; Ran Deng; Meng Li; Binfei Yang; Ruiying Zhu; Li Zhao; Yong Liu; Xiaobo Gong (Journal of Environmental Chemical Engineering, 2025)

Load-carrying mechanism of thin-walled hybrid double-skin tubular columns subjected to axial compression - Ran Deng; Zhe Zhang; Yu Xiang (Engineering Structures, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

Long-term exposure to low-concentration sulfur dioxide and mental disorders in middle-aged and older urban adults - Shenghao Yuan; Yujia Bao; Yongxuan Li; Qingqing Ran; Yanqiu Zhou; Yaqing Xu; Xiaoxi Zhang; Lefei Han; Shi Zhao; Yuzheng Zhang; Xiaobei Deng; Jinjun Ran (Environmental Pollution, 2025)

Machine learning-based strength prediction for circular concrete-filled double-skin steel tubular columns under axial compression - Shou-Zhen Li; Jin-Jin Wang; Liming Jiang; Ran Deng; Yu-Hang Wang (Engineering Structures, 2025)

Phosphorus transformation and bioavailability in livestock manure through aerobic composting and anaerobic digestion - Xueling Ran; Shunjin Li; Naga Sai Tejaswi Uppuluri; Yun Deng; Ya Su; Guangqun Huang; Renjie Dong; Joachim Müller; Quanyuan Wei; Jianbin Guo; Hans Oechsner (Chemical Engineering Journal, 2025)

Synergistic remediation of electroplating wastewater contaminated soil and reduction of risk of groundwater contamination by biochar and Pseudomonas hibiscicola strain L1 - Binbin Ran; Qiang An; Shuman Deng; Jiali Song; Zhiruo Huang; Bin Zhao (International Biodeterioration & Biodegradation, 2025)

Thermoelectric cooling and low-temperature power generation in n-type PbTe enabled by band flattening and entropy engineering - Qian Deng; Jiansen Wen; Xiang An; Yin Xie; Jiaxing Luo; Zhilong Zhao; Baisheng Sa; Hongliang Dong; Ran Ang (Chemical Engineering Journal, 2025)

Phosphorus bioavailability and recycling potential in various organic Waste: Assessment by enzymatic hydrolysis and 31P NMR - Xueling Ran; Naga Sai Tejaswi Uppuluri; Yun Deng; Shengrui Wang; Zhaokui Ni; Jing Hu; Joachim Müller; Renjie Dong; Jianbin Guo; Hans Oechsner (Bioresource Technology, 2025)

Co-hydrothermal carbonization of lignocellulosic biomass and swine manure: Optimal parameters for enhanced nutrient reclamation, carbon sequestration, and heavy metals passivation - Weijie Xiong; Yuping Luo; Wengao Shangguan; Yue Deng; Ronghua Li; Dan Song; Muyuan Zhang; Zengyi Li; Ran Xiao (Waste Management, 2024)

Hazard and pollution characteristics of rock-containing dust in coal mine tunneling faces based on experimental and numerical study - Banghao Zhou; Botao Qin; Qun Zhou; Jian Gan; Zhipeng Deng; Fujun Zhao; Mei Ran; Daowei Sun (Process Safety and Environmental Protection, 2024)

Fe (hydr)oxides and organic colloids mediate colloid-bound chromium mobilization in Cr(VI) contaminated paddy soil - Ting Liu; Ran Wei; Jingjing Li; Weipeng Xie; Shengsheng Sun; Tenghaobo Deng; Shizhong Wang; Yetao Tang; Qingqi Lin; Zhuobiao Ni; Rongliang Qiu (Environmental Pollution, 2024)

Application of Main Controlling Factors for Quantitative Evaluation of a Favorable Carbonate Oil- and Gas-Bearing Area in the Pre-exploration Stage: Lianglitage Formation in the Central Uplift Belt of the Tarim Basin - Bin Li; Junshuai Ran; Tao Tang; Taiyu Deng; Suju Yang; Haitao Lv (Natural Resources Research, 2024)

Biological Classification System Knowledge Graph and Semi-automatic Construction of Its Invertebrate Fossil Branches - Shaochun Dong; Yukun Shi; Yizao Ran; Haijun Wu; Yiying Deng; Junxuan Fan; Xinyu Dai (Journal of Earth Science, 2024)

RETRACTED ARTICLE: Copper Exposure Destroys the Integrity of the Blood-Testis Barrier (BTB) Through p38 MAPK-Meditated Autophagy Pathways - Huidan Deng; Yanbin Lou; Ran He; Junliang Deng; Yanqiu Zhu; Xiaoli Wu; Hongrui Guo (Biological Trace Element Research, 2024)

Selective increase of antibiotic-resistant denitrifiers drives N2O production in ciprofloxacin-contaminated soils - Linfa Fang; Yue Deng; Prakash Lakshmanan; Weibing Liu; Xiufeng Tang; Wenxin Zou; Tong Zhang; Xiaozhong Wang; Ran Xiao; Jinbo Zhang; Xinping Chen; Xiaoxuan Su (Journal of Hazardous Materials, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Pagoda solar evaporators with an alternating hot-cold pattern for rapid, scaling-free desalination of hypersaline brines - Zhenwei Wu; Kai Li; Ran Deng; Yu-Ren Xue; Hao-Nan Li; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2024)

Impact of biochar synergized bacteria on Mn2+ and NH4+-N removal and CO2 immobilization in water by enhanced extracellular electron transfer - Shuman Deng; Qiang An; Weifeng Zhang; Zheng Li; Jiali Song; Yichen Yang; Bohan Xu; Binbin Ran; Bin Zhao (Journal of Environmental Chemical Engineering, 2024)

The process and mechanism of coke gasification dissolution loss in hydrogen-rich blast furnace - Yong Deng; Kuo Yao; Ying Xu; Ran Liu; Zhenghua Huang (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

DNA demethylase Tet2 promotes the terminal maturation of natural killer cells - Yuqing Lin; Biyun Yang; Hailin Liu; Guanghe Ran; Liang Song; Meng Meng; Xiaofeng Yin; Qinghua Bi; Dongmei Yan; Youcai Deng; Yonghui Lu (Immunologic Research, 2024)

Inorganic Carbon Pools and Their Drivers in Grassland and Desert Soils - Longwei Dong; Jinzhi Ran; Jiali Luo; Lin Bai; Ying Sun; Muhammad Aqeel; Yahui Zhang; Xiaoting Wang; Qiajun Du; Junlan Xiong; Haiyang Gong; Qingqing Hou; et al. (Global Change Biology, 2024)
Inorganic carbon is an important component of soil carbon stocks, exerting a profound influence on climate change and ecosystem functioning. Drylands account for approximately 80% of the global soil inorganic carbon (SIC) pool within the top 200 cm. Despite its paramount importance, the components of SIC and their contributions to CO 2 fluxes have been largely overlooked, resulting in notable gaps in understanding its distribution, composition, and responses to environmental factors across ecosystems, especially in deserts and temperate grasslands. Utilizing a dataset of 6011 samples from 173 sites across 224 million hectares, the data revealed that deserts and grasslands in northwestern China contain 20 ± 2.5 and 5 ± 1.3 petagrams of SIC in the top 100 cm, representing 5.5 and 0.76 times the corresponding soil organic carbon stock, respectively. Pedogenic carbonates (PIC), formed by the dissolution and re‐precipitation of carbonates, dominated in grasslands, accounting for 60% of SIC with an area‐weighted density of 3.4 ± 0.4 kg C m −2 at 0–100 cm depth, while lithogenic carbonates (LIC), inherited from soil parent materials, prevailed in deserts, constituting 55% of SIC with an area‐weighted density of 7.1 ± 1.0 kg C m −2 . Soil parent materials and elevation determined the SIC stocks by regulating the formation and loss of LIC in deserts, whereas natural acidification, mainly induced by rhizosphere processes including cation uptake and H + release as well as precipitation, reduced SIC (mainly by PIC) in grasslands. Overall, the massive SIC pool underscores its irreplaceable role in maintaining the total carbon pool in drylands. This study sheds light on LIC and PIC and highlights the critical impact of natural acidification on SIC loss in grasslands.

Associations of long-term exposure to low-level PM2.5 and brain disorders in 260,922 middle-aged and older adults - Ne Qiang; Yujia Bao; Yongxuan Li; Na Zhang; Yanqiu Zhou; Xiaobei Deng; Lefei Han; Jinjun Ran (Chemosphere, 2024)

Fe/Co bimetallic nanozyme disrupting tumorous Self-Regulatory pathways to potentiate ferroptosis - Qing Liu; Qian Chen; Xi Deng; Yutong Zhu; Zhangpeng Shi; Runjie Miao; Ming Ma; Nian Ran; Cheng Li; Hangrong Chen (Chemical Engineering Journal, 2024)

Involvement of CgHSFB1 in the regulation of self-incompatibility in ‘Shatian’ pummelo - Chenchen Liu; Xin Zheng; Jianbing Hu; Qiang Xu; Hao Wen; Zhezhong Zhang; Ran Liu; Xiangling Chen; Zongzhou Xie; Junli Ye; Xiuxin Deng; Lijun Chai (Plant Molecular Biology, 2024)

The Diversity of Artificial Intelligence Applications in Marine Pollution: A Systematic Literature Review - Jia Ning; Shufen Pang; Zainal Arifin; Yining Zhang; U. P. K. Epa; Miaomiao Qu; Jufen Zhao; Feiyang Zhen; Abhiroop Chowdhury; Ran Guo; Yuncheng Deng; Haiwen Zhang (Journal of Marine Science and Engineering, 2024)
Marine pollution, a major disturbance to the sustainable use of oceans, is becoming more prevalent around the world. Multidimensional and sustainable ocean governance have become increasingly focused on managing, reducing, and eliminating marine pollution. Artificial intelligence has been used more and more in recent years to monitor and control marine pollution. This systematic literature review, encompassing studies from the Web of Science and Scopus databases, delineates the extensive role of artificial intelligence in marine pollution management, revealing a significant surge in research and application. This review aims to provide information and a better understanding of the application of artificial intelligence in marine pollution. In marine pollution, 57% of AI applications are used for monitoring, 24% for management, and 19% for prediction. Three areas are emphasized: (1) detecting and responding to oil pollution, (2) monitoring water quality and its practical application, and (3) monitoring and identifying plastic pollution. Each area benefits from the unique capabilities of artificial intelligence. If the scientific community continues to explore and refine these technologies, the convergence of artificial intelligence and marine pollution may yield more sophisticated solutions for environmental conservation. Although artificial intelligence offers powerful tools for the treatment of marine pollution, it does have some limitations. Future research recommendations include (1) transferring experimental outcomes to industrial applications in a broader sense; (2) highlighting the cost-effective advantages of AI in marine pollution control; and (3) promoting the use of AI in the legislation and policy-making about controlling marine pollution.

Paleoenvironmental evolution and organic matter accumulation of the lower Cambrian Maidiping marine black shales in the intracratonic basin, western margin of Sichuan Basin, South China - Guodong Xia; Yuehao Ye; Shugen Liu; Heng Wang; Jinmin Song; Wei Sun; Bo Ran; Kun Jiao; Guoliang Xie; Bin Deng; Zhiwu Li; Yun Zeng (International Geology Review, 2024)

Picea pungens exhibits greatest tolerance to short-time thermal stress compared to Picea abies, and Picea omorika - Fangqun Ouyang; Meng Sun; Xia Cui; Mulualem Tigabu; Hui Zhang; Junyu Deng; Junhui Wang; Yu Wei; Ran He (New Forests, 2024)

Assessing the responses of ecosystem patterns, structures and functions to drought under climate change in the Yellow River Basin, China - Li Zhang; Caiyun Deng; Ran Kang; Huiying Yin; Tianhe Xu; Hermann Josef Kaufmann (Science of The Total Environment, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Promotion of active H-assisted CaCO3 conversion for integrated CO2 capture and methanation - Zongze Lv; Tao Deng; Chang Gao; Yujie Zheng; Chunfei Wu; Jingyu Ran; Changlei Qin (Chemical Engineering Journal, 2024)

Association between long-term ozone exposure and readmission for chronic obstructive pulmonary disease exacerbation - Huajing Yang; Zihui Wang; Yumin Zhou; Zhaosheng Gao; Jing Xu; Shan Xiao; Cuiqiong Dai; Fan Wu; Zhishan Deng; Jieqi Peng; Pixin Ran (Environmental Pollution, 2024)

A novel p-type CoSe2 co-catalyst cooperated with hematite for boosting photoelectrochemical water splitting - Shanshan Jiang; Dabo Liu; Dongke Li; Mengyuan Xiao; Yunchou Deng; Yu Han; Ran Tao; Xiaoxing Fan; Kuiyong Liu (Fuel, 2024)

Multicomponent synergistic flower-like FeS/hollow C fiber for tunable and efficient microwave absorption - Xiaolin Lan; Ran Wang; Wenbo Liu; Zhanhua Huang; Pengyang Deng; Zhijiang Wang (Chemical Engineering Journal, 2024)

The effects of salinity stress on Crassostrea hongkongensis gill morphology, cell proliferation, and apoptosis - Chenyang Yue; Yiting Ran; Chuangye Yang; Salifu Ibrahim; Xinyu Song; Wengang Lü; Yuewen Deng; Qi Li (Aquaculture, 2024)

Identification and comparison of milk fat globule membrane and whey proteins from Selle Français, Welsh pony, and Tieling Draft horse mare’s milk - Kunying Lv; Yixin Yang; Qilong Li; Ran Chen; Liang Deng; Yiwei Zhang; Ning Jiang (Food Chemistry, 2024)

Pull-out behavior of the pre-installed lifting anchor with supplementary reinforcement for the precast concrete segments of wind turbine hybrid towers - Wei Ren; Xu-Hong Zhou; Jing-Shen Wang; Yu-Hang Wang; Ji-Ke Tan; Ran Deng; Yao Lu (Engineering Structures, 2024)

Behavior of super-sized thin-walled CFDST columns for wind turbine towers subjected to combined loads: Experiment - Kai-Yuan Jin; Yu-Hang Wang; Xu-Hong Zhou; Ran Deng; Chao Hu; Hao Wen (Engineering Structures, 2024)

Lateral performance of cold-formed steel framed shear walls using slitted sheathing with stiffeners - Ran Deng; Lu Ye; Yu-Hang Wang; Peng Li; Yu Shi (Engineering Structures, 2024)

Interplay between edaphic and climatic factors unravels plant and microbial diversity along an altitudinal gradient - Muhammad Aqeel; Noreen Khalid; Ali Noman; Jinzhi Ran; Abdul Manan; Qingqing Hou; Longwei Dong; Ying Sun; Yan Deng; Sang Soo Lee; Weigang Hu; Jianming Deng (Environmental Research, 2024)

A deep learning-based method for structural modal analysis using computer vision - Yingkai Liu; Ran Cao; Shaopeng Xu; Lu Deng (Engineering Structures, 2024)

Groundwater Quality and Vulnerability Assessment in a Semiarid Karst Region of Northern China - Ran An; Shu Wang; Zongjun Gao; Zhenyan Wang; Wei Li; Qijun Deng; Lü Lin; Yuanqing Liu (Journal of Earth Science, 2024)

Long-term efficacy and safety of leflunomide combined with low-dose prednisone in treatment of myasthenia gravis: a retrospective study - Li Qiu; Pei Chen; Changyi Ou; Juan Deng; Zhidong Huang; Zhongqiang Lin; Qian Ma; Xin Huang; Lu Yu; Hao Ran; Weibin Liu (Acta Neurologica Belgica, 2024)

Active microbial taxa preferentially assimilate inorganic nitrogen in acidic upland soils using a 15N-DNA-SIP approach - Ran Liu; Cheng Han; Yu Kang; Yunbin Jiang; Huan Deng; Kailou Liu; Jinbo Zhang; Wenhui Zhong (Soil Biology and Biochemistry, 2024)

A two-stage approach to siting electric bus charging stations considering future-current demand - Xinghua Hu; Hao Lei; Dongde Deng; Yuhang Bi; Jiahao Zhao; Ran Wang (Journal of Cleaner Production, 2024)

Cyclic Impact Damage and Water Saturation Effects on Mechanical Properties and Kaiser Effect of Red Sandstone Under Uniaxial Cyclic Loading and Unloading Compression - Kui Zhao; Lin Zhang; Daoxue Yang; Jiefang Jin; Peng Zeng; Xing Wang; Shanhu Ran; Dongming Deng (Rock Mechanics and Rock Engineering, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Responses of soil bacterial and fungal denitrification and associated N2O emissions to organochloride pesticide - Zhi Yang; Yue Deng; Lei Zhong; Ran Xiao; Xiaoxuan Su (Science of The Total Environment, 2023)

The mediating role of AKT/ERK/JNK signaling on the malignant phenotype of microcystin-LR in gastric adenocarcinoma cells - Yinghao Liao; Yali Deng; Xiaojin Yu; Peng Zhang; Ran Liu (Food and Chemical Toxicology, 2023)

A method to obtain scattering phase function based on particle size distribution and refractive index retrieved from Aurora 4000 multi-angle scattering measurements: A numerical study - Liang Ran; Fang Zhou; Zhaoze Deng; Minqiang Zhou; Pucai Wang (Atmospheric Environment, 2023)

Characterization of the Oral Microbiota in Captive Sichuan Golden Snub-nosed Monkeys (Rhinopithecus roxellana) of Different Ages - Rong Chen; Xinyi Liu; Meirong Li; Xiaojuan Xu; Ran Lv; Yuanyuan Chen; Guodong Wang; Changlin Deng; Nan Chen; Ting Jia; Siteng Wang; Guangjin Liu (International Journal of Primatology, 2023)

Effects of different Solanum sect. Solanum (Solanaceae) straw amendments on selenium accumulation and growth of grapevine - Kewen Huang; Xu Chen; Ran Zhang; Yiping Dong; Qunxian Deng; Yan Huang; Lei Liu; Ting Wang; Ming’an Liao; Lijin Lin (Acta Physiologiae Plantarum, 2023)

Efficient rhodamine B dye degradation by red mud-grapefruit peel biochar catalysts activated persulfate in water - Shuman Deng; Maolin Yang; Qiang An; Zheng Li; Bin Zhao; Binbin Ran (Environmental Science and Pollution Research, 2023)

RETRACTED: Variations and driving factors of leaf functional traits in the dominant desert plant species along an environmental gradient in the drylands of China - Muhammad Adnan Akram; Xiaoting Wang; Nawal Shrestha; Yahui Zhang; Ying Sun; Shuran Yao; Jinhui Li; Qingqing Hou; Weigang Hu; Jinzhi Ran; Jianming Deng (Science of The Total Environment, 2023)

Key design and layout factors influencing performance of three-way catalytic converters: Experimental and semidecoupled numerical study under real-life driving conditions - Banglin Deng; Zetao Chen; Chengqi Sun; Shoujun Zhang; Weijiao Yu; Min Huang; Kaihong Hou; Jiaqi Ran; Lili Zhou; Chao Chen; Xinxiang Pan (Journal of Cleaner Production, 2023)

Hotspots and future trends of phosphorus recycling from livestock manure: A bibliometric review - Xueling Ran; Yun Deng; Naga Sai Tejaswi Uppuluri; Bowen Li; Yonghui Zheng; Penghui Chen; Renjie Dong; Joachim Müller; Jianbin Guo; Hans Oechsner (Science of The Total Environment, 2023)

Exploring the repairing mechanisms of reduced graphene oxide (rGo) on the dysregulation of Xenopus Laevis larva hypothalamus-pituitary-thyroid (HPT) axis caused by chiral triazole fungicide metconazole - Yue Deng; Meiling Zheng; Rui Liu; Haixia Zeng; Jingling Diao; Ran Xiao; Xiaoxuan Su (Pesticide Biochemistry and Physiology, 2023)

Experimental study of large-scale stiffened thin-walled CFDST columns under aixal compression - Kai-Yuan Jin; Xu-Hong Zhou; Wei-Dong Ji; Ran Deng; Yu-Hang Wang; Wei Ren (Engineering Structures, 2023)

Intervertebral disc degeneration and inflammatory microenvironment: expression, pathology, and therapeutic strategies - Xin Chen; Zihan Wang; Rongrong Deng; Hongjie Yan; Xin Liu; Ran Kang (Inflammation Research, 2023)

Coupled behaviour and strength prediction of tapered CFDST columns with large hollow ratios for wind turbine towers - Ran Deng; Xu-Hong Zhou; Wei-Dong Ji; Rong-Fu Li; Shuai-Quan Zheng; Yu-Hang Wang (Engineering Structures, 2023)

Geniposide augments apoptosis in fibroblast-like synoviocytes by restoring hypoxia-enhanced JNK-BNIP3-mediated autophagy - Deng Ran; Wang Yan; Bu Yanhong; Wu Hong (Inflammation Research, 2023)

Nitrate_dependent suberization regulates cadmium uptake and accumulation in maize - Anle Chen; Tong Liu; Yan Deng; Ran Xiao; Tong Zhang; Yuan Wang; Yuheng Yang; Prakash Lakshmanan; Xiaojun Shi; Fusuo Zhang; Xinping Chen (Science of The Total Environment, 2023)

Corrigendum to “Long-term environmental levels of microcystin-LR exposure induces colorectal chronic inflammation, fibrosis and barrier disruption via CSF1R/Rap1b signaling pathway” [J Hazard Mater 440 (2022) 129793] - Yue Yang; Hui Wang; Xiaoyan Wang; Ling Chen; Wenya Liu; Danping Cai; Shuxiang Deng; Hanyu Chu; Ying Liu; Xiangling Feng; Jihua Chen; Mengshi Chen; et al. (Journal of Hazardous Materials, 2023)

Comparison of phosphorus species in livestock manure and digestate by different detection techniques - Xueling Ran; Naga Sai Tejaswi Uppuluri; Yun Deng; Yonghui Zheng; Renjie Dong; Joachim Müller; Hans Oechsner; Bowen Li; Jianbin Guo (Science of The Total Environment, 2023)

Influence mechanism of sulfur on dissolutive wetting between molten iron and carbon brick - Yong Deng; Ran Liu; Kexin Jiao; Lida Chen; Yanbo Chen (Journal of Cleaner Production, 2023)

Association between the NEP rs701109 polymorphism and the clinical efficacy and safety of sacubitril/valsartan in Chinese patients with heart failure - Hong-Yu Luo; Li-Chen Gao; Hui-Zhi Long; Zi-Wei Zhou; Shuo-Guo Xu; Feng-Jiao Li; Hong-Li Li; Yan Cheng; Cai-Xia Li; Xing-Yu Peng; Liang Li; Ran Chen; et al. (European Journal of Clinical Pharmacology, 2023)

Effects of different fertilization methods on Lolium multiflorum Lam. growth and bacterial community in waste slag - Boyu Liu; LuYao WeiXie; Ran Deng; Ningfei Lei; Shengyan Pu; Jing Li (Environmental Science and Pollution Research, 2023)

Peanut shell biochar immobilized Pseudomonas hibiscicola strain L1 to remove electroplating mixed-wastewater - Qiang An; Binbin Ran; Shuman Deng; Ningjie Jin; Bin Zhao; Jiali Song; Siyu Fu (Journal of Environmental Chemical Engineering, 2023)

Compressive behavior of the steel–concrete composite adapter for wind turbine hybrid towers - Wei Ren; Ran Deng; Xu-Hong Zhou; Yu-Hang Wang; Feng Cao; Kai-Yuan Jin (Engineering Structures, 2023)

Plant-soil-microbe interactions in maintaining ecosystem stability and coordinated turnover under changing environmental conditions - Muhammad Aqeel; Jinzhi Ran; Weigang Hu; Muhammad Kashif Irshad; Longwei Dong; Muhammad Adnan Akram; Gaber E. Eldesoky; Ahmed Muteb Aljuwayid; Lai Fatt Chuah; Jianming Deng (Chemosphere, 2023)

Insights into the promotion of urine-diverting toilets based on the fertilizer efficiency of artificial phosphate ore recovered from source-separated urine - Yuan Liu; Qi Zhang; Lin-Feng He; Yang Ran; Ying-Ying Deng; Hong Liu (Resources, Conservation and Recycling, 2023)

Late Cretaceous – Cenozoic thermal structure and exhumation of the Eastern Tibetan Plateau margin: A doubly-vergent orogenic wedge - Zhiwu Li; Peter J.J. Kamp; Shugen Liu; Ganqing Xu; Kui Tong; Martin Danišík; Zijian Wang; Jinxi Li; Bin Deng; Bo Ran; Yuehao Ye; Wenhui Wu (Earth-Science Reviews, 2023)

Effects of carbonate minerals and exogenous acids on carbon flux from the chemical weathering of granite and basalt - Chaojun Li; Pete Smith; Xiaoyong Bai; Qiu Tan; Guangjie Luo; Qin Li; Jinfeng Wang; Luhua Wu; Fei Chen; Yuanhong Deng; Zeyin Hu; Yujie Yang; et al. (Global and Planetary Change, 2023)

CH4 and CO2 emissions in water networks of rice cultivation regions - Ouping Deng; Jiangyou Ran; Xuesong Gao; Xiangjun Lin; Ting Lan; Ling Luo; Yalan Xiong; Jiang Liu; Dinghua Ou; Jianbo Fei; Rong Huang (Environmental Research, 2023)

Behaviour of double-corrugated steel plates under cyclic in-plane shear loading: An experimental study - Ran Deng; Jun-De Yang; Yuan Gao; Yu-Hang Wang; Qi-Qi Li (Engineering Structures, 2023)

Impact of urban form on building energy consumption and solar energy potential: A case study of residential blocks in Jianhu, China - Ke Liu; Xiaodong Xu; Ran Zhang; Lingyu Kong; Wei Wang; Wei Deng (Energy and Buildings, 2023)

Biosensor guided effective degradation of anti-nutritional factors via selected soybean fermentation process - Lizhou Ma; Ran Xun; Guohui Li; Yu Deng (Systems Microbiology and Biomanufacturing, 2023)

Comprehensive proteomic and phosphoproteomic reveal that Microcystin-LR contributed to the malignant progression of gastric cancer by estrogenic potency - Peiyan Yang; Peng Zhang; Yali Deng; Yinghao Liao; Xinxin Guo; Mingjun Sun; Lihong Yin; Ran Liu (Environmental Pollution, 2023)

The driving factors and buffering mechanism regulating cropland soil acidification across the Sichuan Basin of China - Aiwen Li; Chengji Li; Yuanyuan Zhang; Qian Deng; Hongyan Fang; Bin Zhao; Min Ran; Liangying Song; Jingling Xue; Qi Tao; Rong Huang; Yiding Li; et al. (CATENA, 2023)

Effect of salinity on greenhouse gas production and emission in marsh soils during the decomposition of wetland plants - Ju Zhang; Jim Jian Wang; Ran Xiao; Huanguang Deng; Ronald D. DeLaune (Journal of Soils and Sediments, 2023)

Effect of Iron Plaque on Gaseous Elemental Mercury Uptake, Translocation, and Volatilization by Paddy Rice - Yanlin Wang; Shuai Shang; Xin Li; Sinan Chen; Ran Li; Weiwei Jia; Hong Deng (Bulletin of Environmental Contamination and Toxicology, 2022)

Paenibacillus hamazuiensis sp. nov., a bacterium isolated from Hamazui hot spring in Yunnan province, south-west China - Juan Wang; Ming Deng; En-Min Zhou; Lei Ran; Cui-Ping Miao; Yi-Qing Li; Jun-Mei Ding; Shu-Kun Tang (Archives of Microbiology, 2022)

Continental‐scale niche differentiation of dominant topsoil archaea in drylands - Weigang Hu; Qingqing Hou; Manuel Delgado‐Baquerizo; James C. Stegen; Qiajun Du; Longwei Dong; Mingfei Ji; Yuan Sun; Shuran Yao; Haiyang Gong; Junlan Xiong; Rui Xia; et al. (Environmental Microbiology, 2022)
Archaea represent a diverse group of microorganisms often associated with extreme environments. However, an integrated understanding of biogeographical patterns of the specialist Haloarchaea and the potential generalist ammonia‐oxidizing archaea (AOA) across large‐scale environmental gradients remains limited. We hypothesize that niche differentiation determines their distinct distributions along environmental gradients. To test the hypothesis, we use a continental‐scale research network including 173 dryland sites across northern China. Our results demonstrate that Haloarchaea and AOA dominate topsoil archaeal communities. As hypothesized, Haloarchaea and AOA show strong niche differentiation associated with two ecosystem types mainly found in China's drylands (i.e. deserts vs. grasslands), and they differ in the degree of habitat specialization. The relative abundance and richness of Haloarchaea are higher in deserts due to specialization to relatively high soil salinity and extreme climates, while those of AOA are greater in grassland soils. Our results further indicate a divergence in ecological processes underlying the segregated distributions of Haloarchaea and AOA. Haloarchaea are governed primarily by environmental‐based processes while the more generalist AOA are assembled mostly via spatial‐based processes. Our findings add to existing knowledge of large‐scale biogeography of topsoil archaea, advancing our predictive understanding on changes in topsoil archaeal communities in a drier world.

Three new unsaturated fatty acids from marine-derived fungus Aspergillus sp. SCAU150 - Ting Zhao; Xiao-Yong Zhang; Ran-Sha Deng; Zhen Tan; Guang-Ying Chen; Xu-Hua Nong (Natural Product Research, 2022)

First-Order Derivatives of Principal and Main Invariants of Magnetic Gradient Tensor of a Uniformly Magnetized Tesseroid and Spherical Shell - Xiao-Le Deng; Wen-Bin Shen; Meng Yang; Michael Kuhn; Jiangjun Ran (Surveys in Geophysics, 2022)

Effects of Pb-, Cd-resistant bacterium Pantoea sp. on growth, heavy metal uptake and bacterial communities in oligotrophic growth substrates of Lolium multiflorum Lam - Luyao WeiXie; Ruilan Yang; Boyu Liu; Ningfei Lei; Shuming Peng; Jingji Li; Jin Tong; Ran Deng; Jing Li (Environmental Science and Pollution Research, 2022)

The anti-angiogenesis mechanism of Geniposide on rheumatoid arthritis is related to the regulation of PTEN - Yanhong Bu; Hong Wu; Ran Deng; Yan Wang (Inflammopharmacology, 2022)

miR-511-5p Suppresses Cell Migration, Invasion and Epithelial–Mesenchymal Transition Through Targeting PAK2 in Gastric Cancer - Wenjing Yong; Ke Zhang; Youming Deng; Weisen Tang; Ran Tao (Biochemical Genetics, 2022)

Substance P modulates BMSCs migration for tissue repair through NK-1R/CXCR4/p-Akt signal activation - Ran Tao; Zhan Qu; Ke Zhang; Jie Chen; Xinyu Wang; Youming Deng (Molecular Biology Reports, 2022)

Genome-wide signatures of mammalian skin covering evolution - Peng Cao; Qinlong Dai; Cao Deng; Xiang Zhao; Shishan Qin; Jian Yang; Ran Ju; Zhiwen Wang; Guoqing Lu; Xiaodong Gu; Zhisong Yang; Lifeng Zhu (Science China Life Sciences, 2021)

Functional connectivity patterns of the subgenual anterior cingulate cortex in first-episode refractory major depressive disorder - Bochao Cheng; Yajing Meng; Yan Zuo; Yi Guo; Xiuli Wang; Song Wang; Ran Zhang; Wei Deng; Yingkun Guo; Gang Ning (Brain Imaging and Behavior, 2021)

First-order derivatives of principal and main invariants of gravity gradient tensor of the tesseroid and spherical shell - Xiao-Le Deng; Wen-Bin Shen; Meng Yang; Jiangjun Ran (Journal of Geodesy, 2021)

Association of gut microbiomes with lung and esophageal cancer: a pilot study - Weitao Shen; Derong Tang; Yali Deng; Huilin Li; Tian Wang; Ping Wan; Ran Liu (World Journal of Microbiology and Biotechnology, 2021)

A Hu sheep genome with the first ovine Y chromosome reveal introgression history after sheep domestication - Ran Li; Peng Yang; Ming Li; Wenwen Fang; Xiangpeng Yue; Hojjat Asadollahpour Nanaei; Shangquan Gan; Duo Du; Yudong Cai; Xuelei Dai; Qimeng Yang; Chunna Cao; et al. (Science China Life Sciences, 2021)

Higher-order gravitational potential gradients by tensor analysis in spherical coordinates - Xiao-Le Deng; Jiangjun Ran (Journal of Geodesy, 2021)

The effect of consecutive ambient air pollution on the hospital admission from chronic obstructive pulmonary disease in the Chengdu region, China - Yi Zhang; Ziyue Wang; Yu Cao; Lifu Zhang; Guan Wang; Fangjie Dong; Ren Deng; Baogen Guo; Li Zeng; Peng Wang; Ruimei Dai; Yu Ran; et al. (Air Quality, Atmosphere & Health, 2021)

Whole-genome resequencing reveals loci with allelic transmission ratio distortion in F1 chicken population - Peng Ren; Feilong Deng; Shiyi Chen; Jinshan Ran; Jingjing Li; Lingqian Yin; Yan Wang; Huadong Yin; Qing Zhu; Yiping Liu (Molecular Genetics and Genomics, 2021)

An improved method used for evaluating potential environmental pollution risk based on spatial distribution and density of farms - Jianghui Wen; Bianyu Zhen; Zhenyu Pu; Xia Peng; Junjun Tan; Zhongbao Shao; Bosheng Bao; Zhiping Ran; Qishuang Gao; Bing Deng (Environmental Science and Pollution Research, 2021)

A Pooled Study of Angiotensin-Converting Enzyme Insertion/Deletion Gene Polymorphism in Relation to Risk, Pathology and Prognosis of Childhood Immunoglobulin A Vasculitis Nephritis - Gao Hui; Zhang Cheng; Hua Ran; Wang Ziwei; Deng Fang (Biochemical Genetics, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Complete mitochondrial genome of Atractomorpha sagittaris (Orthoptera: Pyrgomorphidae) and its phylogenetic analysis for Acrididea - Ran Li; Xiaohan Shu; Wei-an Deng; Ling Meng; Baoping Li (Biologia, 2020)

A Novel Eyes Topical Drug Delivery System: CsA-LNC for the Treatment of DED - Anan Zhang; Rong Sun; Meixin Ran; Yaxin Deng; Ying Ge; Yunjing Zhu; Xiumei Tao; Lixia Shang; Jingxin Gou; Haibing He; Tian Yin; Yanjiao Wang; et al. (Pharmaceutical Research, 2020)

Estimation of PM2.5 Mass Concentration from Visibility - Denghui Ji; Zhaoze Deng; Xiaoyu Sun; Liang Ran; Xiangao Xia; Disong Fu; Zijue Song; Pucai Wang; Yunfei Wu; Ping Tian; Mengyu Huang (Advances in Atmospheric Sciences, 2020)
Aerosols in the atmosphere not only degrade visibility, but are also detrimental to human health and transportation. In order to develop a method to estimate PM 2.5 mass concentration from the widely measured visibility, a field campaign was conducted in Southwest China in January 2019. Visibility, ambient relative humidity (RH), PM 2.5 mass concentrations and scattering coefficients of dry particles were measured. During the campaign, two pollution episodes, i.e., from 4–9 January and from 10–16 January, were encountered. Each of the two episodes could be divided into two periods. High aerosol hygroscopicity was found during the first period, when RH was higher than 80% at most of the time, and sometimes even approached 100%. The second period experienced a relatively dry but more polluted condition and aerosol hygroscopicity was lower than that during the first period. An empirical relationship between PM 2.5 mass concentration and visibility (ambient aerosol extinction) under different RH conditions could thus be established. Based on the empirical relationship, PM 2.5 mass concentration could be well estimated from visibility and RH. This method will be useful for remote sensing of PM 2.5 mass concentration.

Effects of silver(I) toxicity on microstructure, biochemical activities, and genic material of Lemna minor L. with special reference to application of bioindicator - Haibo Li; Fan Mo; Yinghua Li; Mingshuai Wang; Zhe Li; Haiyang Hu; Wenhe Deng; Ran Zhang (Environmental Science and Pollution Research, 2020)

Naturally Occurring Antibodies to Tau Exists in Human Blood and Are Not Changed in Alzheimer’s Disease - Zhong-Yuan Yu; Wei-Wei Li; Hai-Mei Yang; Noralyn B. Mañucat-Tan; Jun Wang; Ye-Ran Wang; Bin-Lu Sun; Zi-Cheng Hu; Li-Li Zhang; Liang Tan; Juan Deng; Yu-Hui Liu (Neurotoxicity Research, 2020)

NIS and epithelial-mesenchymal transition marker expression of circulating tumor cells for predicting and monitoring the radioactive iodine-131 therapy effect in differentiated thyroid cancers - Lei Zheng; Guiyu Wang; Wei Guo; Deng Pan; Laiping Xie; Song He; Chaoxue Luo; Hongmin Li; Yaling Ran; Shiyang Wu; Fang Liu; Xiaoli Zhang; et al. (Molecular Biology Reports, 2019)

Pterostilbene, an active component of the dragon’s blood extract, acts as an antidepressant in adult rats - Liang Yang; Yuanyuan Ran; Zhenzhen Quan; Ran Wang; Qinghu Yang; Qiutian Jia; Heao Zhang; Yanhui Li; Yiheng Peng; JianHua Liang; Hui Wang; Hiroshi Nakanishi; et al. (Psychopharmacology, 2019)

Characteristics and significance of heterogeneity of sea-land transitional facies shale gas reservoir in North Guizhou, China - Ran Wang; Shuxun Sang; Jun Jin; Lingyun Zhao; Wei Gao; Wei Fu; Fulun Shi; Ende Deng (Geosciences Journal, 2019)

Modeling of sediment transport in a saltwater lake with supplemental sandy freshwater - Li Liang; Yun Deng; Ran Li; Jia Li (Environmental Science and Pollution Research, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Response of energy microalgae Chlamydomonas reinhardtii to nitrogen and phosphorus stress - Yizheng Wang; Jiang Yu; Ping Wang; Siwei Deng; Jiahua Chang; Zongxin Ran (Environmental Science and Pollution Research, 2018)

Depositional environment and micropore characteristics of the Ediacaran Doushantuo Formation black shale in Western Hubei, China - Hao Wang; Ziquan Yong; Xuan Zhang; Bo Ran; Di Yang; Chao Luo; Bin Deng (Arabian Journal of Geosciences, 2016)

Knowledge, attitudes, and beliefs of healthcare workers regarding stem cell research - Deng Luo; Wenzhuo Ran; Gongfang Zhao; Chaxiang Guan; Chen Wang; Weiping Jia (Science China Life Sciences, 2016)

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

Promotion of expression of interferon-stimulated genes in U937 monocytic cells by HIV RNAs, measured using stable isotope labeling with amino acids in cell culture (SILAC) - Yulan Li; Bin Wen; Ran Chen; Feng Jiang; Xiaofang Zhao; Xin Deng (Archives of Virology, 2015)

Genetic Association Between APP, ADAM10 Gene Polymorphism, and Sporadic Alzheimer’s Disease in the Chinese Population - Fan Zeng; Cheng Shen; Yu-Hui Liu; Jing Li; Jie Zhu; Ye-Ran Wang; Jia-Chuan Yan; Chang-Yue Gao; Hua-Dong Zhou; Juan Deng; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Serum Aβ is Predictive for Short-Term Neurological Deficits After Acute Ischemic Stroke - Yu-Hui Liu; Hong-Yuan Cao; Ye-Ran Wang; Shu-Sheng Jiao; Xian-Le Bu; Fan Zeng; Qing-Hua Wang; Jing Li; Juan Deng; Hua-Dong Zhou; Yan-Jiang Wang (Neurotoxicity Research, 2015)

Risk factors shared by COPD and lung cancer and mediation effect of COPD: two center case–control studies - Lei Yang; Xiaoxiao Lu; Jieqiong Deng; Yumin Zhou; Dongsheng Huang; Fuman Qiu; Xiaorong Yang; Rongrong Yang; Wenxiang Fang; Pixin Ran; Nanshan Zhong; Yifeng Zhou; et al. (Cancer Causes & Control, 2015)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Late Triassic thickening of the Songpan–Ganzi Triassic flysch at the edge of the northeastern Tibetan Plateau - Shugen Liu; Bin Deng; Luba Jansa; Guozhi Wang; Xianghui Li; Chengshan Wang; Shun Liu; Zhiwu Li; Juchu Li; Wei Sun; Bo Ran (International Geology Review, 2013)

In Vitro and In Vivo Evaluation of Amorphous Solid Dispersions Generated by Different Bench-Scale Processes, Using Griseofulvin as a Model Compound - Po-Chang Chiang; Yong Cui; Yingqing Ran; Joe Lubach; Kang-Jye Chou; Linda Bao; Wei Jia; Hank La; Jonathan Hau; Amy Sambrone; Ann Qin; Yuzhong Deng; et al. (The AAPS Journal, 2013)

Molecular identification and characterization of leucine aminopeptidase 2, an excretory-secretory product of Clonorchis sinensis - Chuanhuan Deng; Jiufeng Sun; Xuerong Li; Lexun Wang; Xuchu Hu; Xiaoyun Wang; Wenjun Chen; Xiaoli Lv; Chi Liang; Wenfang Li; Yan Huang; Ran Li; et al. (Molecular Biology Reports, 2012)

Bivariate genome-wide association study suggests that the DARC gene influences lean body mass and age at menarche - Rong Hai; Lei Zhang; YuFang Pei; LanJuan Zhao; Shu Ran; YingYing Han; XueZhen Zhu; Hui Shen; Qing Tian; HongWen Deng (Science China Life Sciences, 2012)

Functional analysis of pig myostatin gene promoter with some adipogenesis- and myogenesis-related factors - Bing Deng; Jianghui Wen; Yi Ding; Qishuang Gao; Haijun Huang; Zhiping Ran; Yunguo Qian; Jian Peng; Siwen Jiang (Molecular and Cellular Biochemistry, 2012)

High prevalence of a novel porcine bocavirus in weanling piglets with respiratory tract symptoms in China - Shaolun Zhai; Cheng Yue; Zuzhang Wei; Jinxue Long; Duoliang Ran; Tao Lin; Yu Deng; Lv Huang; Lichang Sun; Haihong Zheng; Fei Gao; Hao Zheng; et al. (Archives of Virology, 2010)

Field applications of a bio-trickling filter for the removal of nitrogen oxides from flue gas - Ran Jiang; Shaobin Huang; Jun Yang; Kang Deng; Zhenghui Liu (Biotechnology Letters, 2009)

Epigallocatechin-3-gallate induced primary cultures of rat hippocampal neurons death linked to calcium overload and oxidative stress - Shu-Ting Yin; Ming-Liang Tang; Hong-Min Deng; Tai-Ran Xing; Ju-Tao Chen; Hui-Li Wang; Di-Yun Ruan (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Iron contributes to the formation of catechol isoquinolines and oxidative toxicity induced by overdose dopamine in dopaminergic SH-SY5Y cells - Ran Wang; Hong Qing; Xiao-Qian Liu; Xiao-Lin Zheng; Yu-Lin Deng (Neuroscience Bulletin, 2008)